Pure red-cell aplasia after radioactive iodine treatment in a patient with papillary thyroid cancer and follow up for two years: a case report - Li, Rui; Wang, Meng; Li, Shaoxin; Liao, Lin (Frontiers in Oncology, 2025)
Acquired pure red cell aplasia (PRCA) has attracted more and more attention in hematology. PRCA usually caused by infection, autoimmune diseases, thymic carcinoma, or drugs, has not been reported by radioactive iodine. Here we report a case of PRCA after radioactive iodine therapies (two times, 100 mCi and 130 mCi each) in a patient with papillary thyroid carcinoma and follow up for two years. she was treatment with cyclosporine (100mg twice per day), stanozolol (2mg three times per day) and diammonium glycyrrhizinate (150mg three times per day), returned to the normal range in 2024.